TERAPI OKUPASI MELALUI PENDEKATAN TFA (THINKING, FEELING, ACTING) PADA LANSIA DI PANTI WERDHA WISMA ASIH MADIUN - Masfingatin, Titin; Hanida, Rifa Arma; Putri, Rahel Elsa Dwi; Muhtadi, Abid Humam; Febtalinda, Rizqiana (Universitas Mataram, 2024)
Mental health is a state of well-being/happiness because a person is aware of their own abilities, can cope with the normal stresses of life, works productively and well, and is able to make a contribution to themselves or their community. The elderly must maintain their mental health so they can live a prosperous old age. Aspects that affect the mental health of the elderly include anxiety, depression and dementia (memory decline). The elderly at the Panti Werdha Wisma Asih Madiun have never undergone occupational therapy. The aim of this program is to determine the application of occupational therapy through the TFA (Thinking, Feeling, Acting) approach at the Panti Werdha Wisma Asih Madiun. Methods for implementing activities include preparation, implementation and evaluation. Occupational therapy for the elderly at the Panti Werdha Wisma Asih Madiun using the TFA approach: Thinking with the TTS game, Feeling with elderly yoga exercises, and Acting with making flower bouquets can be carried out well and smoothly. The elderly were very enthusiastic about participating in the activities from start to finish, there was an increase in the number of participants during the program implementation. The success of the program was also demonstrated by the participants' positive response to the activities 83.57%. Occupational therapy using the TFA approach is recommended to be a routine agenda at the Panti Werdha Wisma Asih Madiun in order to achieve mental health for the elderly.